Peak - Smith, Roland (Boston: New York: Clarion Books, Harper Collins Publishers, 2007)
A fourteen-year-old boy attempts to be the youngest person to reach the top of Mount Everest.
Keywords: Mountaineering -- Fiction; Survival -- Fiction; Coming of age -- Fiction; Everest, Mount (China and Nepal) -- Fiction